Analysis of The Character in Doraemon Comic - sadly, afri (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2016)
Literature is an imaginative writing in the sense of fiction. It means that literature is a work that using the writersâ imagination as the topic. The writer can generalize their imagination in several kinds, like story, drama, situation or the result of analysis. Literature means writing valued as work of art. It also refers to the composition that tells stories, dramatizes, situations, expresses emotions, analyzes and advocates. It is clear that in writing literary work the writer usually write in story, drama, situations, express their emotions, and explain an analysis or advocates.This is a descriptive qualitative research. It is a research design part of qualitative method that allows the researcher to describe a phenomenon by presenting the facts in rich detail without attempting to interpret them. Qualitative research is done without give priority in numbers, but focus on the deep understanding to interaction between concepts that is analyzed. It is mean that the qualitative research focuses on the understanding in the concept of the research.In this thesis, the reseach only focused in analyzing the characters in doraemon comicâ Nobita to animal planetâ. For analyzing the characters in doraemon comicâ Nobita to Animal Planetâ the researcher used theory psychological criticism. Psychological criticism there are three parths id, ego and superego. The id is basic character in human, ego is the character that has conjunction with the real situations. character and superego is the personality that contains the values and rules that are evaluative (concerning matters relating to the good and the bad). The researcher want to relate between character with id, ego and superego.Key word: Analysis of the character in doraemon comic.